ANALISIS KONSEP KEADILAN DALAM PELAKSANAAN POLIGAMI - Fatimah Febrianti; Iskandar Iskandar (Muadalah : Jurnal Hukum, 2021)
Polygamy is a husband who has more than one wife, up to four wives. Polygamy has long been carried out where a husband can marry a woman without a limit of number. Then Islam came and limited the number of wives and on the condition that it can be fair. Which has been contained in surah An-Nisaa 'verses 3 and 129. This study aimed to analyze the concept of justice in polygamy according to the Al-Qur'an and Law Number 1 of 1974 concerning Marriage. The main problems in this research are: 1).How was the implementation of justice in polygamy in the perspective of Al-Qur'an? 2) How was the implementation of justice in polygamy in the perspective of Law Number 1 of 1974 concerning Marriage? 3) What was the comparative relationship to justice in polygamy in the perspective of Al- Qur'an and Law Number 1 of 1974 concerning Marriage? This type of research is classified as a library research. Which this study conducted in the library to collect and analyze data sourced from the library.